2021
DOI: 10.1088/2515-7655/abe2f7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of Li diffusivity in LLZO using isotopic exchange and FIB-SIMS

Abstract: Current lithium ion battery technology makes use of flammable liquid electrolytes and so the development of solid ceramic electrolytes for the next generation of all-solid-state batteries can offer a safer alternative. However, the lithium diffusion behaviour in these solid electrolytes is not yet well characterised, despite the importance of this information for optimising cell performance. Similarly, the transport properties at the metal anode interface are critically important, but not well understood. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The self‐diffusion coefficient in solid Li at 25 °C is 7.65 × 10 −11 cm 2 s −1 . [ 36 ] This value is much lower than the Li diffusion in Li 3 Sb with 3.5 × 10 −9 cm 2 s −1 [ 37 ] and LLZO with ≈2 × 10 −9 –8 × 10 −9 cm 2 s −1 [ 38 ] (both at 25 °C). According to Krauskopf et al, [ 35 ] from a physical and chemical point of view, the alloying interlayer fulfils two main functions.…”
Section: Resultsmentioning
confidence: 98%
“…The self‐diffusion coefficient in solid Li at 25 °C is 7.65 × 10 −11 cm 2 s −1 . [ 36 ] This value is much lower than the Li diffusion in Li 3 Sb with 3.5 × 10 −9 cm 2 s −1 [ 37 ] and LLZO with ≈2 × 10 −9 –8 × 10 −9 cm 2 s −1 [ 38 ] (both at 25 °C). According to Krauskopf et al, [ 35 ] from a physical and chemical point of view, the alloying interlayer fulfils two main functions.…”
Section: Resultsmentioning
confidence: 98%
“…However, the limited spatial resolution of neutron detectors requires long diffusion path lengths to characterize the diffusion process. This highlights the importance of multiple techniques for studying Li diffusion processes in solid-state electrolytes, and this an alternative methodology for determining the lithium diffusion coefficients was proposed by Brugge et al 94 This method involves stable tracer experiments, whereby an 6 Li: 7 Li isotope couple (consisting of Li metal and a dense LLZO pellet) is left to inter-diffuse and the resulting isotopic profiles are measured using secondary ion mass spectrometry (SIMS). By using tracer experiments, direct measurement of the diffusion coefficient is possible.…”
Section: Ion Diffusion Characterization Methodologymentioning
confidence: 99%
“…For established non-tracer methods such as impedance spectroscopy and NMR spectroscopy, probing the diffusion and conductivity on different time- and length-scales requires more tracer-based experiments to obtain reliable comparative data. However, in this work, 94 an estimation of the diffusion coefficient was obtained directly by measuring the diffusion length of lithium over a fixed time. Accordingly, this method can be extended to any Li–metal-stable SE or any reactive SE with a stable protective interlayer.…”
Section: Ion Diffusion Characterization Methodologymentioning
confidence: 99%
“…Another type of SIMS spectrometer being used on FIB-based instruments is quadrupole spectrometers. 16 Chater et al. reported a single-column FIB instrument equipped with two quadrupole spectrometers, to detect both positive and negative SIs at the same time.…”
mentioning
confidence: 99%
“…15 Another type of SIMS spectrometer being used on FIBbased instruments is quadrupole spectrometers. 16 Chater et al reported a single-column FIB instrument equipped with two quadrupole spectrometers, to detect both positive and negative SIs at the same time. 17 Nevertheless, these systems work in serial acquisition (meaning that ions of different masses are detected sequentially rather than simultaneously) and are not suitable for fast chemical imaging.…”
mentioning
confidence: 99%